2007
DOI: 10.1002/pssb.200642506
|View full text |Cite
|
Sign up to set email alerts
|

First‐principles study of electronic structure and ground‐state properties of alkali‐metal sulfides – Li2S, Na2S, K2S and Rb2S

Abstract: PACS 71.15. Ap, 71.15.Mb, 71.15.Nc, 71.20.Dg, 71.20.Nr First-principles calculations have been performed to investigate the electronic structure and ground-state properties of alkali-metal sulfides Li 2 S, Na 2 S, K 2 S and Rb 2 S using the tight-binding linear muffin-tin orbital (TB-LMTO) method. At ambient conditions these compounds are found to crystallize in the cubic antifluorite (anti-CaF 2 -type) structure. The exchange correlation energy is described in the local density approximation (LDA) using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
35
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 16 publications
6
35
1
1
Order By: Relevance
“…15 The similar tendency of decrease with atomic mass of X in X 2 S has been also reported on the elastic constants under the same pressure. When the pressure is enhanced, except for the linear decrease of the elastic constant of C 44 , the bulk modulus and the elastic constant of C 11 , C 12 increase in the crystals of Rb 2 S, K 2 S and Na 2 S. Similar trends are also reported in the Li 2 S except for the elastic constants C 44 .…”
supporting
confidence: 56%
“…15 The similar tendency of decrease with atomic mass of X in X 2 S has been also reported on the elastic constants under the same pressure. When the pressure is enhanced, except for the linear decrease of the elastic constant of C 44 , the bulk modulus and the elastic constant of C 11 , C 12 increase in the crystals of Rb 2 S, K 2 S and Na 2 S. Similar trends are also reported in the Li 2 S except for the elastic constants C 44 .…”
supporting
confidence: 56%
“…At low temperatures, the shapes of the curves of C V and C P are similar. As known, the increase of heat capacity with T 3 at low temperatures is due to the harmonic approximation of the [29], c [26], d [20], e [62], f [63], g [64], h [65], i [66], k [67], l [23], m [68], n [69], o [31], p [70]. Debye model.…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
“…In the Na 2 X (X = S, Se) compounds, the metal atoms (Na) are located at (0.25, 0.25, 0.25) and (0.75, 0.75, 0.75) and the atoms (X) are located at (0, 0, 0). These compounds are subjects of many experimental and theoretical works, focusing on structural phase transformation [17][18][19][20][21][22] and electronic properties [23][24][25][26][27]. The electronic band structure of these materials at ambient conditions was discussed [25] using the selfconsistent pseudo-potential method.…”
Section: Introductionmentioning
confidence: 99%
“…A high Pugh B/G ratio is associated with ductility, whereas a low value corresponds to the brittle nature. The critical value which separates ductile and brittle material is 1.75; i.e., if B/G > 1.75, the material behaves in a ductile manner; otherwise the material behaves in a brittle manner [29]. Now we have found that the B/G ratio is 1.54 for this compound, classifying K 2 S as brittle.…”
Section: Elastic Propertiesmentioning
confidence: 61%
“…Schon et al [26] implemented the linear combination of atomic orbitals Hartree-Fock (LCAO-HF) method to analyze high pressure structural phase transition of M 2 S compounds. Selfconsistent pseudopotential method, the LCAO-HF and tight-binding linear muffin-tin orbital (TB-LMTO) studies have been reported by Zhuravlev et al [27], Azavant et al [28], and Eithiraj et al [29], respectively, for electronic band structure of alkali metal sulfides. As well, Khachai et al [20] have calculated the elastic properties of the X 2 S (X = Li, Na, K, and Rb) compounds, under pressure effect, using the full potential augmented plane wave plus local orbitals (FP APW+lo) method.…”
Section: Introductionmentioning
confidence: 99%